Mafia and outlaw stories from Italian life and literature - Pickering-Iazzi, Robin (Toronto Italian studies., 2007)
Mafia and Outlaw Stories from Italian Life and Literature takes a unique and intriguing approach to the subject of the Mafia, and offers informed judgements about its historical impact on Italian society and culture.